Zinc transporter 8 haploinsufficiency protects against beta cell dysfunction in type 1 diabetes by increasing mitochondrial respiration - Yong Kyung Kim; Jay A. Walters; Nicole D. Moss; Kristen L. Wells; Ryan Sheridan; Jose G. Miranda; Richard K.P. Benninger; Laura L. Pyle; Richard M. O'Brien; Lori Sussel; Howard W. Davidson (Molecular Metabolism, 2022)
Objective: Zinc transporter 8 (ZnT8) is a major humoral target in human type 1 diabetes (T1D). Polymorphic variants of Slc30A8, which encodes ZnT8, are also associated with protection from type 2 diabetes (T2D). The current study examined whether ZnT8 might play a role beyond simply being a target of autoimmunity in the pathophysiology of T1D. Methods: The phenotypes of NOD mice with complete or partial global loss of ZnT8 were determined using a combination of disease incidence, histological, transcriptomic, and metabolic analyses. Results: Unexpectedly, while complete loss of ZnT8 accelerated spontaneous T1D, heterozygosity was partially protective. In vivo and in vitro studies of ZnT8 deficient NOD.SCID mice suggested that the accelerated disease was due to more rampant autoimmunity. Conversely, beta cells in heterozygous animals uniquely displayed increased mitochondrial fitness under mild proinflammatory conditions. Conclusions: In pancreatic beta cells and immune cell populations, Zn2+ plays a key role as a regulator of redox signaling and as an independent secondary messenger. Importantly, Zn2+ also plays a major role in maintaining mitochondrial homeostasis. Our results suggest that regulating mitochondrial fitness by altering intra-islet zinc homeostasis may provide a novel mechanism to modulate T1D pathophysiology.